Evaluation of anterior segment biometry parameters in progress and non-progress primary angle closure glaucoma among Malays and Chinese - Fang, Neoh Pei (2017)
Background: Primary angle closure glaucoma (PACG) is the second most common type of glaucoma in Asia, and the main cause of glaucoma blindness. PACG is believed to progress faster among Asians. Identification of patients at risk of progression is crucial to reduce the morbidity and disease burden. Most knowledge of burden, risk factors and epidemiology about PACG has been derived from high risk populations such as Chinese, Japanese and Indians populations. Both Malay and Chinese comprise the majority population in Malaysia. Ethnic differences in PACG progression may exist; Malays have been found to present with worst visual acuity and progression compared to Chinese residing in Malaysia. Anterior segment biometry parameters such as axial length have been associated with progression of PACG. As anterior segment biometry has been found to be associated with progression, we aimed to investigate these parameters in Malays and to.compare these parameters between the two major ethnicity in Malaysia. Objective: The aim of this study were to compare anterior segment biometry parameters in progress and non-progress PACG among Malays and Chinese. Methods: This was a cross-sectional study involving 75 patients (43 Malay PACG patients and 32 Chinese PACG patients) recruited from 1 glaucoma centre in Malaysia recruited between November 2015 and December 2016. Ocular examination included axial length (AL) and anterior chamber depth (ACD) measurement using a noncontact partial coherence interferometer (IOL Master, Carl Zeiss, Germany). Anterior chamber angle (ACA), measuredby Anterior Segment-OCT (Cirrus, Carl Zeiss, Germany). Humphrey visual field (HVF) 24-2 analysis of the same eye was done and used to evaluate glaucoma progression. Patients were categorized into two groups: those with progression and those without. Comparison of anterior segment biometry parameters between Malay and Chinese PACG patients with and without progression was analysed using independent T test and multivariate ANOVA analysis. Results: Chinese PACG patients had shorter AL (22.18mm±0.76) and narrower ACA (11.09°±1.31) than Malay PACG patients. There was no significant difference between the ACD of Malay and Chinese PACG patients. After adjustment for confounding factors., only ACA was significantly difference. Among patients with progression, all the anterior segment biometry parameters (AL, ACD, ACA) were significantly different between Malays and Chinese. However, after controlling for confounding factors, there was no significant difference, In the group without progression, no significant differences in anterior segment biometry parameters were observed between the two ethnic groups. Malay PACG patients with progression had narrower Anterior Chamber Angle (ACA) (11.96°±6.00) compared to non-progressing patients. Axial Length (AL) and Anterior Chamber Depth (ACD) did not differ significantly between Malay patients with and without progression. Conclusion: There was racial influence in ocular biometry measurement in PACG patients. Chinese has significant narrower ACA compared to Malays. Serial AS-OCT monitoring is important in management of PACG. Evaluating anterior segment biometry parameters is essential in predicting risk of progression in Malay PACG. Further researches and larger studies need tobe conducted before we can further conclude the association of the anterior segment biometry parameters with progression of PACG.